Determinanţi ai calităţii vieţii pacienţilor de etnie romă, din perspectiva mediatorilor sanitari - Roman, Gabriel; Gramma, Rodica; Enache, Angela-Mariana; Pârvu, Andrada-Viorica (Calitatea Vieții, 2012)
The Roma represent an important ethnic minority in Romania, who often face inequalities in their access to health care. The policies and the strategies that focused on reducing this inequalities and a better inclusion of the Roma have lead to the establishment of a sanitary mediators network, that is currently operating in Roma communities, thus facilitating a better communication between this particular minority and the health care professionals, as well as an improved access to healthcare services. Our study – Determinants of the quality of life of the Roma patients, from the perspective of the health mediators – focuses on identifying the determinants of the quality of life of Roma patients, and it is based on three group interviews with sanitary mediators, in the counties of Iasi and Cluj. The results indicate that, when it comes to health care services, doctors should be familiar with and aware of the cultural background of the community, their values and traditions. Communication based on respect, the development of a partnership between doctors and patients, avoiding racial labeling and prejudices are the most important requirements of the Roma, because their dignity and quality of life should not be affected under the conditions of the interaction with healthcare professionals. The activity of health mediators, persons who are familiar with members of the community, with their customs and traditions, has a positive potential in assuring the quality of life.